(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Changes of relative volume of parenchyma and stroma as well as the processes of morphological reconstructions of reticular fibers in regenerating liver of rats and domestic hens after partial hepatectomy have been studied. It was shown that dynamics and character of changes of these parameters in hens and rats submit to the general regularities.